Comparison between Airway Responses to High versus Low Molecular Weight Compounds in Occupational Asthma. (25th May 2011) - Talini, D.; Novelli, F.; Bacci, E.; Dente, F. L.; De Santis, M.; Di Franco, A.; Melosini, L.; Vagaggini, B.; Paggiaro, P. L.
Abstract : Occupational asthma (OA) is a heterogeneous disease, and the characteristics of the sensitizer responsible for OA may induce different clinical, functional, and biological manifestations. We examined the characteristics of 74 patients with OA induced by low molecular weight compounds (LMWC) or by high molecular weight compounds (HMWC) and diagnosed by specific inhalation challenge (SIC). Patients with OA induced by LMWC had a longer occupational exposure before the beginning of symptoms, a lower sputum eosinophilia, and a higher prevalence of late airway response (LAR), in comparison with patients with OA induced by HMWC. Pulmonary function tended to be poorer and atopy tended to be less frequent in LMWC-induced OA than in HMWC-induced OA. These data confirm and extend previous observations showing that the characteristics of the specific sensitizer inducing OA may determine different clinical, functional, and biological features, probably related to the difference pathogenetic mechanisms underlying these different types of OA.